A speculative conversation on climate change and sociology (Sociologisk Forskning, 2023)
This article provides a diverse range of insights into the question of how sociology can and should contribute to research on climate change. It takes an unconventional and unique approach to doing so, through a stylized conversation between the authors, which is based on an open-ended focus group discussion. The conversation illuminates different perspectives on if and how to research climate change and the climate crisis from a sociological perspective. We delve into issues of normativity in sociological research, discuss the benefits and pitfalls of several methodological approaches, theorize about how climate change might affect sociology in the decades to come, as well as how sociology needs to further develop in order to stay a relevant discipline for this grand societal challenge. We conclude not with suggestions for future research, but with a call for further reflective conversation on these topics, both within and outside of sociology.
Keywords: normativity; philosophy of science; climate crisis; climate sociology; future of sociology